2012
DOI: 10.1111/j.1471-6712.2012.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with rehabilitation in relation to self‐perceived quality of life and function among patients with stroke – a 12 month follow‐up

Abstract: Scand J Caring Sci; 2013; 27; 373–379 Satisfaction with rehabilitation in relation to self‐perceived quality of life and function among patients with stroke – a 12 month follow‐up Background and Purpose:  Stroke causes complex disability and function, and perceived quality of life has been shown to correlate with satisfaction with care as well as with life in general among stroke patients. The aim of this study was to study the relation of satisfaction with how rehabilitation was provided with self‐perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In previous studies where post-stroke QoL was measured [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], the utility measurement varied between 0.47 and 0.88 ( Table 4 ), which could be explained by the fact that the follow-up times varied greatly between studies (from 3 months to 5 years) and that the type of stroke evaluated was different from one study to another. These publications showed that patients with a better QoL, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies where post-stroke QoL was measured [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], the utility measurement varied between 0.47 and 0.88 ( Table 4 ), which could be explained by the fact that the follow-up times varied greatly between studies (from 3 months to 5 years) and that the type of stroke evaluated was different from one study to another. These publications showed that patients with a better QoL, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study highlight the need for programs to improve the physical activities of stroke patients. According to Hansson et al, functional independence is an important factor that influences HRQoL of stroke patients 26 ) . In the anxiety/depression dimension of the results, the mean values for stroke were higher than those of the other diseases; however, the differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…It also related to emotional distress and unmet care needs [5,6]. Better health outcomes and quality of life were associated with higher satisfaction with stroke care and rehabilitation [3,[6][7][8][9]. Previous studies on patient satisfaction six months after stroke showed that the highest rates of dissatisfaction were related to stroke care, rehabilitation, information, and services after discharge [10,11].…”
Section: Introductionmentioning
confidence: 99%